2022
DOI: 10.21037/jtd-22-226
|View full text |Cite
|
Sign up to set email alerts
|

Lung recruitment after cardiac arrest during procurement of atelectatic donor lungs is a protective measure in lung transplantation

Abstract: Background: Brain-dead donors are susceptible to pulmonary atelectasis (AT). In procurement surgery, lung recruitment under circulatory conditions and cold-flushing for atelectatic donor lungs often provoke graft injury due to the acute blood inflow. We hypothesized that lung recruitment without blood circulation can mitigate graft injury. This study aimed to examine the benefits of lung recruitment subsequent to cardiac arrest using a porcine lung-transplant model.Methods: Thirteen donor pigs were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…While conditions were similar among all the groups this reaffirms that lung injury perhaps occurred while the atelectatic lungs were inflated under blood perfused conditions within the donor (4).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…While conditions were similar among all the groups this reaffirms that lung injury perhaps occurred while the atelectatic lungs were inflated under blood perfused conditions within the donor (4).…”
supporting
confidence: 55%
“…In the present manuscript Niman et al (4), have demonstrated that lung recruitment after cardiac arrest during donor lung procurement has a protective effect on both the donor lung as well as following transplant. The authors should be congratulated for their efforts to study an innovative method to mitigate donor lung damage during procurement and for the novel concept.…”
mentioning
confidence: 58%
“…Tidal volume should be kept at 6 to 8 ml/kg as part of a lungprotective ventilation strategy. Prior to donor lung retrieval, hemodynamic and metabolic goals should be kept intact [94,95].…”
Section: Intraoperative Assessmentmentioning
confidence: 99%
“…Recipient animal outcome during the first 6 hours was compared between two study groups following implantation of a 24-hour atelectatic left donor lung. The parenchyma was fully recruited either before versus after cardioplegic circulatory arrest prior to the start of cold pulmoplegia (25). The authors reported that posttransplant oxygenation capacity expressed as PaO 2 /FiO 2 ratio was significantly better in the group with lungs not recruited until after circulatory arrest (P=0.015).…”
Section: Temperature During Cold Static Preservationmentioning
confidence: 99%